Whose Side Is It On? – The Boundaries Dispute in the North Malacca Strait - Bernard, Leonardo (UI Scholars Hub, 2012)
The waters in North Malacca Strait are one of a number of areas between Indonesia and Malaysia where no clear boundaries exist. Currently, there is an agreement on boundaries of the continental shelf between Indonesia and Malaysia in the area, but as yet there is no agreement on the boundaries for the Exclusive Economic Zone (EEZ). The lack of clear boundaries makes it difficult for either State to effectively exercise control over the body of water, not only with regard to fishing activities, but also with regard to environmental and security issues. This paper will discuss the history of the regime of the continental shelf, the Agreement on Continental Shelf Boundaries between Indonesia and Malaysia and the development of the international regimes for the EEZ and the continental shelf under the United Nations Convention on the Law of the Sea (UNCLOS). It will then discuss the importance for Indonesia and Malaysia of having clear EEZ boundaries in the North Malacca Strait.